Diagnostic performance of Gd-EOB-DTPA-enhanced MRI for evaluation of liver dysfunction: a multivariable analysis of 3T MRI sequences - Verloh, Niklas (Oncotarget, 2018)
OBJECTIVE: The aim of this study was to evaluate the diagnostic performance of a multiparametric gadolinium ethoxybenzyl-diethylenetriaminepentaacetic acid (Gd-EOB-DTPA)-enhanced MRI examination for the estimation of liver dysfunction classified by the Model for End-Stage Liver Disease (MELD) score. RESULTS: Liver dysfunction can be assessed by different methods. In a logistic regression analysis, T1- and T2-weighted images were affected by impaired liver function. In the assessment of liver dysfunction, the reduction rate in T1 mapping sequences showed a significant correlation in simple and multiple logistic regression. CONCLUSION: Changes in Gd-EOB-DTPA-enhanced MRI between plain images and images obtained during the hepatobiliary phase allowed good prediction of liver dysfunction, especially when using T1 mapping sequences. MATERIALS AND METHODS: A total of 199 patients underwent contrast-enhanced MRI with a hepatocyte-specific contrast agent at 3T. In the multivariable analysis, the full range of available MRI sequences was used to estimate the liver dysfunction of patients with various MELD scores.